Neuropsychomotor developmental delay: conceptual map, term definitions, uses and limitations - Lílian de Fátima Dornelas; Neuza Maria de Castro Duarte; Lívia de Castro Magalhães (Sociedade de Pediatria de São Paulo, 2015)
OBJECTIVE: To retrieve the origin of the term neuropsychomotor developmental delay" (NPMD), its conceptual evolution over time, and to build a conceptual map based on literature review. DATA SOURCE: A literature search was performed in the SciELO Brazil, Web of Science, Science Direct, OneFile (GALE), Pubmed (Medline), Whiley Online, and Springer databases, from January of 1940 to January of 2013, using the following keywords: NPMD delay, NPMD retardation, developmental delay, and global developmental delay. A total of 71 articles were selected, which were used to build the conceptual map of the term. DATA SYNTHESIS: Of the 71 references, 55 were international and 16 national. The terms developmental delay and global developmental delay were the most frequently used in the international literature and, in Brazil, delayed NPMD was the most often used. The term developmental delay emerged in the mid 1940s, gaining momentum in the 1990s. In Brazil, the term delayed NPMD started to be used in the 1980s, and has been frequently cited and published in the literature. Delayed development was a characteristic of 13 morbidities described in 23 references. Regarding the type of use, 19 references were found, with seven forms of use. Among the references, 34 had definitions of the term, and 16 different concepts were identified. CONCLUSIONS: Developmental delay is addressed in the international and national literature under different names, various applications, and heterogeneous concepts. Internationally, ways to improve communication between professionals have been indicated, with standardized definition of the term and use in very specific situations up to the fifth year of life, which was not found in Brazilian publications.